Autonomic dysfunction as a possible cause of sudden cardiac death in swimming sports - Dostal, Jiri; Hybska, Tereza; Saganelidze, Khatuna; Pudil, Radek; Stasek, Josef (Frontiers in cardiovascular medicine, 2024)
INTRODUCTION: Human diving reflex is a well-studied phenomenon. However, very little is known about the possible relationship between augmented diving reflex and autonomic dysfunction. METHODS: We retrospectively studied a group of four swimmers who underwent a diving reflex test as part of the examination due to symptoms related to autonomic dysfunction during swimming. The control group comprised 11 healthy swimmers with no history of these symptoms. A standardized diving reflex test was performed for each athlete in both groups. Hemodynamic profiles, including heart rate, stroke volume, and cardiac output, were recorded. RESULTS: There were no statistically significant differences between the groups in any of the three parameters measured before the test. However, at the end of the test, each parameter (heart rate, stroke volume, and cardiac output) was significantly lower in the swimmers who presented with clinical symptoms related to autonomic dysfunction than in the control group. CONCLUSION: This observation could shed light on autonomic dysfunction as a possible cause of sudden cardiac death in swimming athletes. It also demonstrated that autonomic dysfunction is presented not only by decreased heart rate but also by stroke volume, causing a drop in cardiac output to the level of hemodynamic collapse.
Keywords: hemodynamics; syncope; autonomic dysfunction; diving reflex; bradycardia; sudden cardiac death